Analisis Faktor Pengetahuan, Sumber Daya dan Usia yang Mempengaruhi Keinginan dan Perilaku UMKM Pengrajin Bambu Dalam Penerapan Digitalisasi Pencatatan Akuntansi - Fitri, Syarifah Massuki; Suandi, Suandi; Mawaddah, Nur Aulia; Rizqina, Intan (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines the influence of knowledge, resources, and age on the intention and behavior of bamboo craft MSMEs in Tamansari Village toward the digitalization of accounting records. The research is motivated by the increasing urgency of accounting digitalization to enhance financial data accuracy, facilitate real-time information access, and minimize manual recording errors—despite ongoing adoption challenges among bamboo craftsmen. Using a descriptive quantitative approach, data were collected through a survey involving 52 respondents representing 26 bamboo craft MSMEs selected using random sampling. The results reveal that, partially, only age has a significant influence on MSME owners’ intention to adopt digitalization, while knowledge and resources do not show a significant effect. However, regarding behavior, all three variables significantly affect digitalization practices. Interestingly, knowledge and resources demonstrate a negative relationship with behavior, suggesting that higher awareness and resource availability may increase the perception of risks—such as cost, system maintenance, and data security—which in turn reduces the likelihood of adoption. Conversely, age has a strong positive relationship, as younger entrepreneurs are more adaptive and willing to experiment with new technologies. This study contributes to the literature by emphasizing the importance of behavioral readiness and risk perception in digital adoption among MSMEs, extending the understanding beyond the traditional focus on skills and infrastructure. Practically, the findings highlight the need for broader digitalization strategies that not only provide training or technical assistance but also address perceptual and attitudinal barriers, foster digital trust, and integrate policy-level support to encourage inclusive and sustainable digital transformation within MSME ecosystems.